Effects of an introduced crayfish, Procambarus clarkii, on the distribution of southâ€western Iberian amphibians in their breeding habitats (Ecography, 2006)
The introduction of exotic species in aquatic habitats is one of the causes for the amphibian declines observed worldwide. In the 1970s, the red swamp crayfish Procambarus clarkii was introduced in the southwest Iberian Peninsula, where no native crayfish occur. In this study we assess the effect of P. clarkii presence in the breeding site distribution of each of the 13 southwest Iberian amphibians, while simultaneously accounting for the effects of potentially confounding habitat variables, as well as for the effects of the other large aquatic predators in the study area predatory fish. Amphibian species richness was lower in places where P. clarkii was present than in places without P. clarkii, regardless of fish presence. After accounting for habitat variables and fish, crayfish presence was a negative predictor of the breeding probability for all urodeles (Pleurodeles waltl, Salamandra salamandra , Triturus boscai and T. marmoratus) and for two anurans (Pelobates cultripes and Bufo bufo). The majority of the species affected usually breed in temporary ponds without fish, but that may be colonized by the crayfish. The ongoing expansion of P. clarkii may eventually lead to a growing isolation of amphibian populations and ultimately to local extinctions and a permanent alteration of the amphibian communities in southwest Iberian Peninsula.